The Identical Grammatical Elements In Surat Al-Baqara - Their Benefits And Effects - Saber ismail hamza qadir (QALAAI ZANIST JOURNAL, 2020)
This linguistic research studies the syntactic elements in the Qur’anic sentence in Surat Al-Baqara, In this study, the researcher relied on the phenomenon of “congruence” in language, which is the major grammatical phenomenon for its dependence on: presumption: (number: singular, and twofold, and plural), (type: masculine, and feminine), and (appointment): unidentified and identified), and (the parsing: Al-Rrafe, Al-Naseb, and Al-Jarr), and the function of each of these clues is to involve two grammatical elements that are inseparable and more to coincide with them, to strengthen the link between them. Consequently, the reader or interpreter reaches the most accurate meanings of those elements that are identical in their contexts as it seems that each of these four clues is distributed among other smaller clues, without departing from the function of conjunction: (The main) is the same as the original one, as a presumptive function: (the number) matches two grammatical elements that are inseparable or more in: (singularity, twofold, or plural), The function of presumption: (the type) is the same, but in: (masculinization or feminization), and the function of presumption: (appointment) is the involvement of two syntactic and more grammatical in: (identified or unidentified) and the context of articulation is very much the same. However, its function is weaker than the peers, as it is a verbal context on the body of syntactic and non-syndic elements in the Arabic sentences –this is the consistent structures of the Arabic sentences, whether Quranic or non-Quranic, and a special feature of this language that distinguishes them from other languages.